Penerapan Metode Dempster Shafer dalam Mendiagnosa Penyakit Pneumonia - Muhammad Rafi Fadhilah; Agung Triayudi (STMIK Budi Darma, 2024)
The aim of this research is to apply the Dempster Shafer Method in diagnosing pneumonia. This research aims to apply the Dempster Shafer Method in diagnosing pneumonia. The main problem faced in the diagnosis of this disease is the complexity and uncertainty in the interpretation of symptoms and medical test results. Dempster Shafer's method, a method in belief theory that allows combining information from multiple sources with different levels of certainty, was proposed as a solution to overcome this uncertainty. In this study, symptom data and medical test results from patients suspected of suffering from pneumonia were collected. Then, the Dempster Shafer Method is applied to combine information from various sources, such as blood test results, lung X-rays, and the patient's medical history. This method makes it possible to establish the level of confidence in the resulting diagnosis. The research results show that the application of the Dempster Shafer Method in diagnosing pneumonia provides more accurate results compared to traditional approaches. By considering the uncertainty and complexity in diagnosis, the Dempster Shafer Method is able to provide more reliable estimates and help doctors make more appropriate decisions in treating pneumonia cases. Application of the Dempster Shafer Method also produces a framework that can be adapted to diagnose other diseases that require managing uncertainty. Additionally, this approach can help increase efficiency in the diagnosis process, leading to a reduction in diagnostic errors and an improvement in the overall quality of patient care. Thus, this research makes an important contribution to the development of more sophisticated and reliable diagnostic methods in the medical field. The results of analysis using the Dempster-Shafer method show that the maximum value for each combination of symptoms that is important in diagnosing pneumonia is 0.9811, which is equivalent to 98.11%. Based on this interpretation, it is estimated that the patient has a high chance of suffering from severe pneumonia.